Akulturasi Unsur Kungfu Tiongkok dalam Pencak Silat Betawi - Sufianto, Agustinus; Lim, Sugiato; Khosasih, Andyni (Bina Nusantara University, 2015)
This study aimed to examine the influence of acculturation of Chinese Kungfu elements on Pencak Silat Betawi. The study used qualitative method and observation with interview and literature study by looking up Betawi and Pencak Silat on Batavia literature. Research finds out that the origins and influence of acculturation of Chinese Kungfu in Pencak Silat Betawi can be seen from a reciprocal relationship between the Chinese community and Betawi through the exchange of knowledge between Chinese martial arts champion and Betawi champion, or brought directly by Chinese Muslims as Master Ong and Kwee Tang Kiam. In addition, there are elements of acculturation both in naming or some movements adopted from Chinese kungfu as Chinese way in Maen Pukul Sabeni that uses two fingers (index and middle), the use of symbols that are closely related to Chinese culture symbols in the logo of Pencak Silat Sabeni, respect technique with Baoquan Li shape as in Mustika Kwitang, and so on.